Islands, maps, and Lontara’; Bugis counter-mapping on a nineteenth-century map of Nusantara - Perdana, Aditya Bayu; Buana, Muhammad (Wacana, Journal of the Humanities of Indonesia, 2023)
This article focuses on a Bugis nautical chart of Nusantara (the Malay Archipelago) from the early nineteenth century known as the Utrecht Map. There are only a few surviving copies of similar Bugis maps, all confiscated from local “pirates” during the colonial era. While graphical elements of the map undoubtedly point to prototypical European maps, careful analysis of its annotations reveals extensive linguistic modification better to reflect Bugis maritime knowledge. Not only are they completely written in Lontara’, the indigenous script of the Bugis, Euro-centric toponyms from contemporaneous maps are consistently replaced by locally derived toponyms from an oral and written tradition unknown to Europeans. In colonial frameworks, maps could be used as powerful instruments of control which eroded indigenous spatial knowledge. As part of an ongoing efforts to decolonize our understanding of maps, critique of western maps should be complemented by discussions of non-western maps which foreground indigenous knowledge or counter-mapping elements. The use of indigenous elements can be regarded as a fascinating case of counter-mapping and a decolonial effort initiated by the anonymous, everyday people of Nusantara.